CREATIVITY OF WILHELM KIESEWETTER TRANSLATOR, ARTIST-ETHNOGRAF ON THE BASIS OF TRAVELING TO THE CRIMEA - PANOV, Serhii (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2019)
The article deals with issues related to the work of the then outstanding Berlin translator, artist and ethnographer Wilhelm Kiesewetter. «The desire to present to the wider public a variety of looks, mores and customs of different, less known and less cultural tribes prompted me to study them during many years of travel and reliably display pictures of their life on the spot.” The result of his travels was a collection of ethnographic travel sketches, which consists of embossed images and canvases painted with oil paints. The article presents important elements of creativity of the traveler, translator, artist and ethnographer. The purpose of the article is to highlight some stages of his stay in the Crimea, to show an example of everyday scenes of children and teachers in school, to reveal his talent of knowledge of other worlds. Research methods: theoretical and historical analysis, synthesis of scientific literature. His philosophical reflection of reality is based on his experiences through the world of pictures and models of reality.